Identification of Determinants Factors of Cultural Based Destination Branding Design for Trowulan - Anggrianto, Christian (VCD: Journal of Visual Communication Design, 2016)
By the increasingly high levels of tourism object competition nowadays, then each region must have the sensitivity and the ability to be able to explore their potentials in order to improve their society’s living standards. One of the great potential that Indonesia have that has not really managed well is in the tourism sector, Indonesia has a wide range of natural resources and could be potentially empowered as a tourism sector, however, currently it is still hard to be achieved. Frequently, we can find the tourism objects in Indonesia is packaged as it is without having a unique value that distinguishes one to another. As one of the examples is the Trowulan, a small town in East Java has a great potential of cultural tourism which has not been packaged properly. Trowulan, once was the Centre of a great kingdom of Majapahit, many physical cultural relics as well as non-physical that is still preserved. Therefore to preserve the uniqueness of Trowulan as a cultural tourism area to be managed well, a process of brand destination is required.